Teacher-Parent Collaboration in Supporting Children with Speech Delays: A Case Study in East Kalimantan Plantation Community - Situmeang, Sri Lasri Yohana; Suparno, Suparno (Journal of Innovation and Research in Primary Education, 2025)
Speech delays affect 5-10% of preschool children and require collaborative intervention approaches. Limited research exists on teacher-parent collaboration models in rural communities for addressing early childhood communication challenges. This study investigated teacher-parent collaboration patterns in supporting children with speech delays aged 5-6 years within a plantation community setting.  A qualitative descriptive study was conducted at TK Anugerah Abadi 1, East Kalimantan, involving 20 parents and 3 teachers. Data collection employed interviews, observations, field notes, and documentation review. Methodological triangulation ensured data validity, while thematic analysis identified collaboration patterns and intervention strategies.  Three primary collaboration modes emerged: quarterly home visitations, school-based meetings, and continuous digital communication. Direct face-to-face interaction predominated, facilitated by the compact plantation community structure. Collaborative content focused on developmental progress, behavioral observations, and intervention strategies. Environmental factors, including COVID-19 restrictions and excessive screen time exposure, contributed to speech delays. The three-tiered intervention approach successfully improved children's communication abilities and enhanced parental knowledge. Parents reported increased confidence in supporting language development following collaborative education sessions. However, scheduling challenges due to parents' work demands required weekend meeting arrangements. Effective teacher-parent collaboration for speech delay intervention requires sustained, multifaceted approaches combining direct communication, environmental adaptation, and targeted parent education. The plantation community's geographic proximity facilitated intensive collaboration but may limit generalizability to other settings. Future research should examine collaboration sustainability and effectiveness across diverse community contexts to develop scalable intervention models.